2012
DOI: 10.2308/jiar-10221
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mandatory Adoption of IFRS on Earnings Quality: Evidence from the European Union

Abstract: This paper addresses the question whether the mandatory adoption of International Financial Reporting Standards (IFRS) is associated with higher accounting quality. More specifically, we investigate whether the application of IFRS in 15 European Union (EU) countries is associated with less earnings management and higher timeliness, conditional conservatism, and value relevance of accounting numbers. Our results suggest that there has been some improvement in accounting quality between the pre- and post-IFRS ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
4
25

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 53 publications
7
93
4
25
Order By: Relevance
“…In this vein, among the central research question which was examined by previous research is: Have mandatory adoption of IFRS improves earnings quality by constraining management earnings discretion [2] in the E.U countries, namely France? Through literature review, we found two principal shortcomings about this issue: The first shortcoming is that the prior literature (such as Capkun et al 2008, Zeghal et al 2012) on the impact of mandatory IFRS adoption on earnings management has concentrated mainly on the discretionary accruals as measure of earnings management. However, earnings management can be also undertaken by managers based on real transactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, among the central research question which was examined by previous research is: Have mandatory adoption of IFRS improves earnings quality by constraining management earnings discretion [2] in the E.U countries, namely France? Through literature review, we found two principal shortcomings about this issue: The first shortcoming is that the prior literature (such as Capkun et al 2008, Zeghal et al 2012) on the impact of mandatory IFRS adoption on earnings management has concentrated mainly on the discretionary accruals as measure of earnings management. However, earnings management can be also undertaken by managers based on real transactions.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical studies provide results variously. Research conducted by Barth et al (2008), Armstrong et al (2010, Wang andCampbell (2012), Zeghal et al (2012) and Chua et al ( 2012) conclude that the adoption of IFRS can improve the quality of accounting information which is measured by a decrease in profit. Meanwhile study conducted by Lin and Paananen (2006), Callao and Jarne (2010) and Rudra and Bharttachrjee (2012) conclude conflicting results stating that earnings management conducted by companies has increased after the adoption of IFRS.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Selain itu ada juga argumentasi bahwa IFRS dapat meningkatkan kualitas informasi akuntansi karena penggunaan fair value lebih dapat merefleksikan kondisi ekonomik perusahaan (Barth et al 2008). Penelitian tentang efek adopsi IFRS mandatory yang dilakukan oleh Zeghal et al (2012) Kousenidis et al (2010), Kwong (2010), Outa (2011), Chua et al (2012 dan Zeghal et al (2012) menjelaskan kualitas informasi akuntansi yang tinggi diindikasikan dengan adanya hubungan yang kuat antara harga atau return saham dengan laba dan nilai buku ekuitas karena kedua informasi akuntansi tersebut mencer-minkan kondisi ekonomi perusahaan. Selanjutnya hasil penelitian yang dilakukan oleh Lev (1989) menyatakan bahwa value relevance sangat erat hubungannya dengan kualitas laba, sehingga penggunaan reaksi pasar sekuritas untuk mengukur kualitas laba mulai banyak digunakan.…”
Section: International Financial Reporting Standards (Ifrs) Yang Sebeunclassified
“…Jika nilai Adjusted R 2 meningkat maka kualitas informasi akuntansi juga meningkat setelah adopsi IFRS (Barth et al 2008;Outa 2011;Chua et al 2012;Zeghal et al 2012). Pada Tabel 3 menunjukkan terdapat kenaikan Adjusted R 2 .…”
Section: Hasil Dan Pembahasanunclassified